Religiosity element in young Muslim profesional accountability - Mohd Zin, Mohamad Zaid; Hamzah, Azimi; Suandi, Turiman; Krauss, Steven Eric; Mohamed Shaffril, Hayrol Azril (2015)
Accountability issues have attracted worldwide discussion, particularly with respect to the contribution of Western scholars. In addition, the existing theories failure to assess the suitability of the existing accountability issues, lead the higher probability to evaluate the accountability in religiosity (Islamic) view which are holistic (syumul). Therefore, this paper reviews the relevant of religiosity element in influencing the young Muslim professional performance in the workplace. It also intend to the existence of various negative elements in the young Muslim professional’s accountability. A number of discussions have been highlighted and it is a hope that it can contribute fresh ideas to the existing literatures.